A uniqueness result for the fractional Schrödinger-Poisson system with strong singularity - Wang Li; Chen Renhua; Zhong Qiaocheng; Wang Jun; Li Fang (Open Mathematics)
This article considers existence of solution for a class of fractional Schrödinger-Poisson system. By using the Nehari method and the variational method, we obtain a uniqueness result for positive solutions.